PENGARUH KEPERCAYAAN MEREK TERHADAP LOYALITAS PELANGGAN MEMBELI SHAMPO MEREK PANTENE - CAHYANINGTYAS, ELOK (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2016)
The aim of this research is to determine simultaneous and partial influence of trust brand on the loyalty of student of the Faculty of Economics, Tadulako University, Palu to buy Pantene Shampoo. Sampling method in this research is purposive sampling; with a total sample of 96 respondents. The results of hypothesis testing using F-test show that the three independent variables that are brand trust(X) consisting of brand characteristics (X1), the characteristics of the company (X2) and the characteristics of customers with the brand (X3) simultaneously have positive and significant influence on the dependent variable customer loyalty (Y) with sig-F of 0.000 <0.05. Furthermore, the brand characteristic variable (X1) with sig 0,001, characteristic of the company (X2) with sig of 0.001, and characteristics of customers to the brand value of sig 0.004 <0.05, which shows partial influence on customer loyalty variable (Y). R2 values of 0.645 and brand belief variable (X) simultaneously influence customer loyalty (Y) of 64.5%, while the remaining 35.5% is influenced by other factors that are not examined.